EYSENCK’S VIEW ON THE PSYCHOLOGY AND PSYCHOBIOLOGY OF INDIVIDUAL DIFFERENCES - Martínez Selva, José María (Anales de Psicología / Annals of Psychology)
This paper examines those aspects of Eysenck’s personality theory that are of interest for the psychobiologists. On one hand, the importance of the psychobiology theory and data in the construction and development of his theory is underlined. On the other hand, it is reviewed the great amount of studies carried out in order to biologically validate his theory, especially in what regards the Introversion-Extraversion and the Neuroticism-Control dimensions.